Inkerinsuomalaisten karkotus, hajaannus ja vastarinta Stalinin ajan Neuvostoliitossa aikalaiskirjeiden ja muistitiedon valossa - Reuter, Anni (Helsingin yliopisto, 2023)
Deportations, Diaspora and Resistance during Stalin's Time in the Letters and Oral Histories of Ingrian Finns. Dissertation. In my doctoral dissertation, I investigated the interpretation of Ingrian Finns on their history of mass deportations, diaspora, and resistance in the Soviet Union during Stalin’s time. My research material consisted of 170 letters from the 1930s, other archival material, and oral histories. The deportation of Ingrian Finns began in the 1930s in the Soviet Union with the forced relocation of ‘kulak’ peasants, dissident thinkers, and their families. From 1935, Finnish nationality became a major reason for deportation. Approximately, 45,000 Ingrian Finns were deported in the 1930s from Ingria, the historical area surrounding St. Petersburg, to the Kola Peninsula, Siberia, Central Asia, and other peripherical exile areas. During the Second World War, approximately 28,000–30,000 Finns were deported from the Siege of Leningrad mostly to distant areas in Siberia, because of their Finnish nationality. Ingrians Finns returning from Finland (56,000) were deported past Ingria to central Russia. I analysed research material with theoretical concepts and methods of diaspora, silent resistance, counter-narratives, family genealogy, and total deportations. I found out: (1) The totality of forced deportations of Ingrian Finns manifested in their oral histories and life cycles. Deportations emptied Ingria of Ingrian Finns during Stalin’s rule from 1930 to 1942. Destroying of Ingrian Finnish culture, forced work, work army, and restrictions of living areas were a part of the total deportation. Oral histories told almost forgotten deportations of Ingrian Finns, from Ingria in 1947, from Estonia in 1948, the Karelian border area in 1950 and other. Ingrian Finns who had been in Finland during the Continuation War were deported past Ingria to Central Russia without the right to move, although promised to return home in Ingria. Deportation was described in oral histories as a hoax and forced deportation. ...